Optical response of the Cu2S2diamond core in Cu2II(NGuaS)2Cl2 - Witte, Matthias; Grimm-Lebsanft, Benjamin; Goos, Arne; Binder, Stephan; Rübhausen, Michael; Bernard, Martin; Neuba, Adam; Gorelsky, Serge; Gerstmann, Uwe; Henkel, Gerald; Schmidt, Wolf Gero; Herres-Pawlis, Sonja (Journal of Computational Chemistry)

Surface vibrational Raman modes of In:Si(111)(4×1)and(8×2)nanowires - Speiser, E.; Esser, N.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)

Temperature-Dependent Hole Mobility and Its Limit in Crystal-Phase P3HT Calculated from First Principles - Lücke, Andreas; Ortmann, Frank; Panhans, Michel; Sanna, Simone; Rauls, Eva; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry B)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Grand canonical Peierls transition in In/Si(111) - Jeckelmann, Eric; Sanna, Simone; Schmidt, Wolf Gero; Speiser, Eugen; Esser, Norbert (Physical Review B)

Rare-earth silicide thin films on the Si(111) surface - Sanna, S.; Dues, C.; Schmidt, Wolf Gero; Timmer, F.; Wollschläger, J.; Franz, M.; Appelfeller, S.; Dähne, M. (Physical Review B)

Density functional theory of the CuA-like Cu2S2 diamond core in Cu 2II(NGuaS)2Cl2 - Witte, M.; Gerstmann, Uwe; Neuba, Adam; Henkel, G.; Schmidt, Wolf Gero (Journal of Computational Chemistry)

Atomic size effects studied by transport in single silicide nanowires - Miccoli, I.; Edler, F.; Pfnür, H.; Appelfeller, S.; Dähne, M.; Holtgrewe, K.; Sanna, S.; Schmidt, Wolf Gero; Tegenkamp, C. (Physical Review B)

A Bifunctional Electrocatalyst for Oxygen Evolution and Oxygen Reduction Reactions in Water - Schöfberger, Wolfgang; Faschinger, Felix; Chattopadhyay, Samir; Bhakta, Snehadri; Mondal, Biswajit; Elemans, Johannes A. A. W.; Müllegger, Stefan; Tebi, Stefano; Koch, Reinhold; Klappenberger, Florian; Paszkiewicz, Mateusz; Barth, Johannes V.; et al. (Angewandte Chemie International Edition)

Manipulation resolves non-trivial structure of corrole monolayer on Ag(111) - Tebi, Stefano; Aldahhak, Hazem; Serrano, Giulia; Schöfberger, Wolfgang; Rauls, Eva; Schmidt, Wolf Gero; Koch, Reinhold; Müllegger, Stefan (Nanotechnology)

Vergleichende Betrachtung von Software-Werkzeugen zur Geschäftsmodellentwicklung - Strotmeyer, Sebastian; John, Thomas; Kundisch, Dennis (Multikonferenz Wirtschaftsinformatik (MKWI))

Vergleich von Disambiguierungsansätzen bei Anforderungsbeschreibungen - Vollmers, Daniel

Delayed (de-)activation in servers with a sleep mode - Herlich, Matthias; Bredenbals, Nico; Karl, Holger (Sustainable Computing: Informatics and Systems)

Surface induced vibrational modes in the fluorescence spectra of PTCDA adsorbed on the KCl(100) and NaCl(100) surfaces - Paulheim, A.; Marquardt, C.; Sokolowski, M.; Hochheim, M.; Bredow, T.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (Physical Chemistry Chemical Physics)
We report a combined experiment-theory study on low energy vibrational modes in fluorescence spectra of perylene-3,4,9,10-tetracarboxylic acid dianhydride (PTCDA) molecules.

Impurity-Mediated Early Condensation of a Charge Density Wave in an Atomic Wire Array - Yeom, Han Woong; Oh, Deok Mahn; Wippermann, Stefan; Schmidt, Wolf Gero (ACS Nano)

Fast Dynamic Fault Injection for Virtual Microcontroller Platforms - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Becker, Markus; Kleinjohann, Bernd; Scheytt, Christoph (Proceedings of the IEEE/IFIP International Conference on VLSI (VLSI-SOC))
Electronic systems, like they are embedded in road vehicles, have to be compliant to functional safety standards like ISO 26262 [1], which limit the impacts of malfunctions for safety critical systems. ISO 26262, for instance, defines different safety levels for road vehicles, which require different means and measures for a safety compliant system and its development process like risk analysis and fault effect simulation. For fault effect simulation it is important to investigate the impact of physical and hardware related effects to the correct function of a system. This article first studies code and model mutations for fault injection in the context of fault effect simulation through different system abstraction levels. It demonstrates how high level mutations correlate to bit flips of software binaries by examples from the TriCore™ instruction set and finally presents a virtual platform based implementation for automated injection of bit flip based mutations into software binaries. Experimental results demonstrate the efficiency of the implemented approach.

An all-transmission-line 220 GHz differential LNA in SiGe BiCMOS - Mao, Yanfei; Schmalz, Klaus; Scheytt, Christoph; Shiju, E. (IEEE International Symposium on Radio-Frequency Integration Technology)
This paper presents a four stage all-transmission-line 220 GHz differential LNA in SiGe BiCMOS technology. Cascode topology is chosen for each stage. The amplifier takes advantage of microstrip transmission lines to realize the inductive load, Marshand balun, input, output, and inter-stage matching of the LNA. The LNA has a gain of 21 dB at 224 GHz, a 3 dB bandwidth of more than 6 GHz. It has a supply voltage of 3V and power dissipation of 234 mW. The amplifier is intended for the use in communication, security scanning, imaging and remote sensing at 220 GHz.

Fault Injection and Mixed-Level Simulation for Analog Circuits - A Case Study - Abughannam, Saed; Wu, Liang; Müller, Wolfgang; Scheytt, Christoph; Ecker, Wolfgang; Novello, Christiano (Analog 2016 - VDE)
The design of safety critical systems requires an efficient methodology for an effective fault effect simulation for analog and digital circuits where analog fault injection and fault effect simulation is currently a field of active research and commercial tools are not available yet. This article begins by discussing fault injection strategies for analog circuits applied on a case study with two topologies of a Voltage Controlled Oscillator (VCO). In the second part it performs on the basis of the example of a Wireless Sensor Network (WSN) node, how far different mixed level implementations with Verilog-A and SPICE can affect the simulation time and points out which component consumes the major part of the simulation time.

Obstacle detection using a miniaturized radar sensor operating at 120GHz ISM band - Nava, Federico; Genschow, Dieter; Scheytt, Christoph (DRONE Berlin 2016)
Currently, all drone manufactures face the same problem: flight safety utility will become mandatory to obtain the legal admission for broad commercial use of drones. This means that on-board obstacle detection and collision avoidance is a must-have in order to overcome existing legal barriers and acceptance issues. Some of the currently available sensors are too large, too heavy, or can be poorly integrated into existing systems. During the exhibition a demonstration of a novel micro-sensor operating at 120 GHz will be given and participants will have the chance to experience the device first-hand.

Linear ultra-broadband NPN-only analog correlator at 33 Gbps in 130nm SiGe BiCMOS technology - Javed, Abdul Rehman; Scheytt, Christoph; Von der Ahe, Uwe (IEEE Bipolar/BiCMOS Circuits and Technology Meeting)
An ultra-broadband analog correlator consisting of a four-quadrant multiplier and an ultra-fast resettable integrator using only NPN transistors was designed, fabricated, and measured. For the integrator, a cross-coupled transistor pair is used as a negative resistance generator. A novel ultra-fast reset circuit is implemented which allows to reset the integrator within very short time of 120 ps. The chip was fabricated using 130 nm SiGe BiCMOS technology with fT of 250 GHz and f max of 300 GHz. In the measurements carried out on printed circuit board, the correlator operated without noticeable performance degradation with inputs up to 33 Gbps which correspond to a bandwidth of more than 24 GHz. The correlator exhibits high linearity with output P1dB of more than 9.9 dBm (700 mV diff ) for both inputs. It dissipates 122.5 mW for the core circuit excluding the 50 Ω output driver. To the knowledge of the authors, the circuit represents the fastest analog correlator published so far. It can be used for spread spectrum communication, radar signal processing, and measurement applications.